LC-MS-Based Metabolomic Approach Revealed the Significantly Different Metabolic Profiles of Five Commercial Truffle Species - Li, Xiaolin; Zhang, Xiaoping; Ye, Lei; Kang, Zongjing; Jia, Dinghong; Yang, Lufang; Zhang, Bo (Frontiers in Microbiology, 2019)
Truffles are ascomycetous ectomycorrhizal fungi that have elevated status in the culinary field due to their unique aroma and taste as well as their high nutritional value and potential biological activities. Tuber melanosporum, T. indicum, T. panzhihuanense, T. sinoaestivum, and T. pseudoexcavatum are five commercial truffle species mainly distributed in Europe or China. In this study, an untargeted metabolomics technology based on an ultra high-performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS) method was applied to analyze the metabolic profiles and variations among these five truffle species. A total of 2376 metabolites were identified under positive ion mode, and the total expression levels of these metabolites were higher in T. melanosporum. Principal component analysis (PCA) and partial least squares-discriminant analysis (PLS-DA) revealed a clear separation from each of these five truffles, and 1282 metabolites with significantly differential expression were detected. These differential metabolites covered various chemical categories, and a detailed analysis was performed for nine metabolic categories, including amino acids, saccharides and nucleosides, organic acids, alkaloids, flavonoids, carnitines, phenols and alcohols, esters, and sulfur compounds. The results showed that for each of the nine categories, the numbers of metabolites with the greatest accumulation in T. melanosporum were the maximum compared with the other four truffles. There were significant differences in the average expression intensity in each category among the five truffles, e.g., higher expression of amino acids was detected in T. panzhihuanense and T. pseudoexcavatum; T. indicum contained significantly more carnitines, while there were more alkaloids in T. melanosporum. Additionally, some metabolites with biological activities were discussed for each category, such as acetyl-L-carnitine, adenine, neobavaisoflavone, and anandamide. In total, 110 pathways or metabolisms covered by the differential metabolites were detected based on KEGG. This study may provide valuable information regarding the variation of the metabolic composition of these five commercial truffle species, and the biological significance of these metabolites was uncovered to explore the metabolic mechanisms of truffles, which would be helpful for further research on the compounds and potential biological functions in truffles that have not yet been investigated.